Fault diagnosis in a networked control system under communication constraints: A quadrotor application - Chabir, Karim; Sid, Mohamed Amine; Sauter, Dominique (Zielona Góra: Uniwersytet Zielonogórski)
This paper considers the problem of attitude sensor fault diagnosis in a quadrotor helicopter. The proposed approach is composed of two stages. The first one is the modelling of the system attitude dynamics taking into account the induced communication constraints. Then a robust fault detection and evaluation scheme is proposed using a post-filter designed under a particular design objective. This approach is compared with previous results based on the standard Kalman filter and gives better results for sensor fault diagnosis.
Keywords: networked control systems; transmission delays; robust residual generation; adaptive residual evaluation